Entrepreneurial Psychology and Motivation of Museum Cultural and Creative Product Development - Qi, Ji; Song, Chaoli; Wang, Yan (Frontiers in Psychology, 2021)
More students majored in design should be led to be self-employed, who can use their major advantages to lead cultural and creative industries of museums toward a more creative direction. Based on present situation of self-employment of college students related to cultural and creative industries, developing pattern and structure of cultural and creative industries of museums are analyzed to study the practical requirement of development of creative and cultural products of museums on the students majored in design. College students and graduates (within 2 years) in design major of a college in Zhejiang province who have experience in starting business are invited to make the questionnaire survey, to study the practical problems with motives and barrier of starting business. After the investigation of the entrepreneurial status of cultural and creative entrepreneurs of college students, it is found that the third year is the peak period for students to choose entrepreneurship, followed by the end of the senior year. Only 36.8% respondents are satisfied with the results of entrepreneurship, which reflects that entrepreneurs do face many obstacles in the actual process of entrepreneurship, mainly due to lack of experience and funds. The motivation for students to stick to entrepreneurial activities mainly focuses on "obtaining personal wealth" and "realizing self-worth". In view of this situation, universities, society, and government can provide technical support and policy support to stimulate the entrepreneurial potential of cultural and creative entrepreneurs of college students, thus promoting the efficient development of museum cultural and creative industry.